2019
DOI: 10.18632/aging.102523
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mortality predictors and incidence of breast cancer

Abstract: Measures derived using blood DNA methylation are increasingly under investigation as indicators of disease and mortality risk. Three existing epigenetic age measures or "epigenetic clocks" appear associated with breast cancer. Two newly-developed epigenetic mortality predictors may be related to all-cancer incidence, but associations with specific cancers have not been examined in large studies. Using HumanMethylation450 BeadChips to measure blood DNA methylation in 2,773 cancer-free women enrolled in the Sist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 57 publications
3
28
1
Order By: Relevance
“…However, for both PhenoAge and GrimAge , there was overall little attenuation of risk estimates after adjustment for a comprehensive set of sociodemographic and lifestyle cancer risk factors, which may indicate that these measures capture information beyond self-reported questionnaires and on many adverse environmental and lifestyle factors that affect the methylome over the life course. To our knowledge, no data exist on the association of PhenoAge and GrimAge with risk of cancers other than pancreatic cancer ( 29 ) and breast cancer; in the latter case, the Sister Study revealed a reasonably strong association with PhenoAge ( 30 ) (invasive disease; hazard ratio per 5-year increase: 1.13, which is of similar magnitude to our findings for colorectal, kidney, lung, mature B-cell, and urothelial cancers) ( Supplementary Table 4 , available online) but not with GrimAge ( 31 ). Further adjustment for estimated white blood cell proportions slightly attenuated associations with cancer risk overall, although a larger association was observed for GrimAge and lung cancer, similar to observations made for PhenoAge and risk of breast ( 30 ) and pancreatic cancer ( 29 ).…”
Section: Discussionsupporting
confidence: 80%
“…However, for both PhenoAge and GrimAge , there was overall little attenuation of risk estimates after adjustment for a comprehensive set of sociodemographic and lifestyle cancer risk factors, which may indicate that these measures capture information beyond self-reported questionnaires and on many adverse environmental and lifestyle factors that affect the methylome over the life course. To our knowledge, no data exist on the association of PhenoAge and GrimAge with risk of cancers other than pancreatic cancer ( 29 ) and breast cancer; in the latter case, the Sister Study revealed a reasonably strong association with PhenoAge ( 30 ) (invasive disease; hazard ratio per 5-year increase: 1.13, which is of similar magnitude to our findings for colorectal, kidney, lung, mature B-cell, and urothelial cancers) ( Supplementary Table 4 , available online) but not with GrimAge ( 31 ). Further adjustment for estimated white blood cell proportions slightly attenuated associations with cancer risk overall, although a larger association was observed for GrimAge and lung cancer, similar to observations made for PhenoAge and risk of breast ( 30 ) and pancreatic cancer ( 29 ).…”
Section: Discussionsupporting
confidence: 80%
“…However, because of the moderate correlation between DNAm ages, and chronological age, it is not surprising to find predictive power of DNAm clocks for the prevalence, and incidence of age-related health outcomes. Recent studies have revealed that age acceleration (AA), which is the raw residual in the linear regression model with DNAm age regressed on chronological age, is a candidate biomarker for all-cause death, and age-related diseases [13] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . The well documented AA measures are epigenetic age acceleration of intrinsic, and extrinsic (i.e., IEAA, and EEAA) [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Horvath et al showed that PhenoAgeAccel, and GrimAgeAccel had strong predictive power for all-cause death, coronary heart disease, and cancer [13] . However, most related studies, to date, focused on IEAA, and EEAA [17] , [18] , [19] , [20] , and few investigated the associations between PhenoAgeAccel / GrimAgeAccel and multiple health endpoints [ 13 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 For example, three studies involving breast cancer examined the association between DNAm age acceleration and breast cancer incidence. 67,68,77 Two of the studies reported a statistically significant association between DNAm age acceleration and the incidence of postmenopausal invasive cancers of the breast, with no ductal carcinoma in situ association. 67,68 One breast cancer study showed that DNA methylation age estimated by DNAm GrimAge had only a weak positive association with invasive cancers.…”
Section: Dnam Age Acceleration Mortality and Age-related Diseasesmentioning
confidence: 99%
“…67,68 One breast cancer study showed that DNA methylation age estimated by DNAm GrimAge had only a weak positive association with invasive cancers. 77 Two studies involving lung cancer also showed inconsistent results. 71,78 In contrast, two studies of colorectal cancer reported that DNAm age acceleration is significantly associated with colorectal cancer.…”
Section: Dnam Age Acceleration Mortality and Age-related Diseasesmentioning
confidence: 99%